Economic instruments for managing industrial waste in Malaysia - Hassan, Mohd Nasir; Rafia, Afroz; Mohamed, Ahmad Fariz; Awang, Muhamad (Environmental Management Society Malaysia, 2005)
Rapid development process of manufacturing industry in Malaysia has resulted to increasing amount of industrial and hazardous waste generation. It is recognized that industrialization has economic, environmental and social trade-offs.Where there are trade-offs between environmental preservation and economic development, several alternatives are employed to mitigate those harmful effects.Such actions are required under the existing and currently reviewed environmental laws and regulations and proposed economic incentives. In the past Malaysia emphasized the economic benefits of development. Now there is an emphasis on the environment. The Government of Malaysia should consider that like many developed countries, the use of appropriate economic tools and incentives in order to achieve a resilient developed country. These instruments are needed to encourage environmentally responsible decision-making by investors, consumers and other economic actors